Scalable High‐fidelity Growth of Semiconductor Nanorod Arrays with Controlled Geometry for Photovoltaic Devices Using Block Copolymers. Issue 21 (24th July 2014) - Pelligra, Candice I.; Huang, Su; Singer, Jonathan P.; Mayo, Anthony T.; Mu, Richard R.; Osuji, Chinedum O.
<x xml:space="preserve">Abstract</x> Controlled density semiconducting oxide arrays are highly desirable for matching nanometer length scales specific to emerging applications. This work demonstrates a facile one‐step method for templating hydrothermal growth which provides arrays with high‐fidelity tuning of nanorod spacing and diameter. This solution‐based method leverages the selective swelling of block copolymer micelle templates, which can be rationally designed by tuning molecular weight and volume fraction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>